Genome analysis identifies differences in the transcriptional targets of duodenal versus pancreatic neuroendocrine tumours - Yuliang Chen; Tobias Else; Juanita L Merchant; Yana Zavros; David C Metz; Jayati T Chakrabarti; Karen Rico; Suzann Duan; Ritu L Pandey; Julie Starr; Bryson W Katona (BMJ Open Gastroenterology)
Objective Gastroenteropancreatic neuroendocrine tumours (GEP-NETs) encompass a diverse group of neoplasms that vary in their secretory products and in their location within the gastrointestinal tract. Their prevalence in the USA is increasing among all adult age groups.Aim To identify the possible derivation of GEP-NETs using genome-wide analyses to distinguish small intestinal neuroendocrine tumours, specifically duodenal gastrinomas (DGASTs), from pancreatic neuroendocrine tumours.Design Whole exome sequencing and RNA-sequencing were performed on surgically resected GEP-NETs (discovery cohort). RNA transcript profiles available in the Gene Expression Omnibus were analysed using R integrated software (validation cohort). Digital spatial profiling (DSP) was used to analyse paraffin-embedded GEP-NETs. Human duodenal organoids were treated with 5 or 10 ng/mL of tumor necrosis factor alpha (TNFα) prior to qPCR and western blot analysis of neuroendocrine cell specification genes.Results Both the discovery and validation cohorts of small intestinal neuroendocrine tumours induced expression of mesenchymal and calcium signalling pathways coincident with a decrease in intestine-specific genes. In particular, calcium-related, smooth muscle and cytoskeletal genes increased in DGASTs, but did not correlate with MEN1 mutation status. Interleukin 17 (IL-17) and tumor necrosis factor alpha (TNFα) signalling pathways were elevated in the DGAST RNA-sequencing. However, DSP analysis confirmed a paucity of immune cells in DGASTs compared with the adjacent tumour-associated Brunner’s glands. Immunofluorescent analysis showed production of these proinflammatory cytokines and phosphorylated signal transducer and activator of transcription 3 (pSTAT3) by the tumours and stroma. Human duodenal organoids treated with TNFα induced neuroendocrine tumour genes, SYP, CHGA and NKX6.3.Conclusions Stromal–epithelial interactions induce proinflammatory cytokines that promote Brunner’s gland reprogramming.